MENGENAL KONSEP BILANGAN MENGGUNAKAN MEDIA PERMAINAN DADU PADA ANAK USIA DINI - Ais Larasati, Dedi Aryadi, Yusdiana (JURNAL PENDIDIKAN DAN PENELITIAN SERUMPUN MENGAJAR, 2024)
This classroom action research aims to improve children's ability to recognize the concept of numbers using dice as a media game for children aged 4-5 years in PAUD BIna Ananda, Binuang sub-district, the method used in this research is the Lewin model. This method is carried out in four stages, namely planning, implementation, observation and reflection. The subjects of observation were students aged 4-5 years at PAUD Bina Ananda, totaling 15 children, and the object of this research was the ability to recognize number concepts in children aged 4-5 years. The data collection technique uses observation and documentation as well as data analysis using descriptive qualitative, the indicators set are at least 70% of the 15 children studied have the ability to recognize the concept of numbers well. This research was conducted in two cycles. The results of the research show that understanding the concept of numbers in children aged 4-5 years at PAUD Bina Ananda shows improvement. The increase in understanding the concept of numbers in children aged 4-5 years at the time of pre-research showed results of 38.3% and experienced an increase in cycle I of 48.3. Because the value obtained had not reached the predetermined criteria, the next action was carried out, namely cycle II action and experienced a good increase with a score of 75%. Because the predetermined results had been achieved, the research was stopped because it had reached the success criteria.